MINIMAL PAIRS AND ITS INFLUENCE TOWARD STUDENTS PRONUNCIATION IN ENGLISH FRICATIVE SOUNDS - Rahman Taufiqrianto Dako (Jurnal Inovasi, 2008)
The aim of this paper is to describe the way to overcome students difficulties in pronouncing some English fricatives / f, v, , , , , s, z/ by using minimal pairs. Minimal pairs are two different forms are identical in every way expect for one sound segment that occurs in the same place in the string. Fricatives are formed by narrowing of the air passage at the some points so that, when air is expelled by pressure from lungs, it escapes with a kind of hissing sound. English fricatives sounds are given in a couple sounds and explained how to produce them in order to the students know the differences and easy to pronounce English fricatives.